Uji Aktivitas Antioksidan Ekstrak Metanol Bunga dan Daun Patikala (Etlingera elatior (Jack) R.M.Sm) Menggunakan Metode DPPH - Handayani, Virsa; Ahmad, Aktsar Roskiana; Sudir, Miswati (Pharmaceutical Sciences and Research, 2014)
Patikala (Etlingera elatior (Jack) R.M.Sm) is a plant of the Zingiberaceae family. Patikala (E. elatior (Jack) R.M.Sm) have bioactive compounds are flavonoids that act as antioxidants. The purpose of this study was to measure free radical activity in the methanol extract of the fruit and leaves Patikala (E. elatior (Jack) R.M.Sm). Extraction of flowers and leaf samples by maceration method using methanol. Qualitative analysis of chemical compounds with certain eluent using Thin Layer Chromatography (TLC) to determine the group of active compounds in the extract. Antioxidant activity assay using the immersion method of DPPH (1,1-Diphenyl-2-picryl Hidrazil) measured absorption at a wavelength of 517 nm and compared with the power of antioxidant quersetin. The results showed that the methanol extract rendemen is at 1.935% for flowers and leaves at 5.17%. Antioxidant activity of the methanol extract of the flowers patikala (E. elatior (Jack) R.M.Sm) have low antioxidant activity with the value IC50 101.84 mg / mL and methanol extracts of leaves Patikala (E. elatior (Jack) R.MSm) have strong antioxidant activity with value IC50 30,65 mg / mL. This potential is lower than that of quercetin IC50 value of 5.35 mg / mL.